2017
DOI: 10.1007/s00330-017-4796-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal forceps biopsy in patients suspected of having malignant biliary obstruction: factors influencing the outcomes of 271 patients

Abstract: • Percutaneous forceps biopsy provides relatively high accuracy in diagnosis of malignant biliary obstructions. • The predictive factors of false-negative biopsy were biopsy site and origin of primary tumour. • The procedure-related complications were low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
3
18
3
4
Order By: Relevance
“…ICC versus HCC.-The differential diagnosis of ICC from HCC is critical as those two disease entities have different treatment strategies and prognoses (119)(120)(121). Considering that HCC can be noninvasively diagnosed without the requirement of pathologic confirmation in high-risk patients (122,123), misdiagnosis of ICC as HCC on imaging studies may lead radiologists to skip histologic confirmation leading to improper treatment.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…ICC versus HCC.-The differential diagnosis of ICC from HCC is critical as those two disease entities have different treatment strategies and prognoses (119)(120)(121). Considering that HCC can be noninvasively diagnosed without the requirement of pathologic confirmation in high-risk patients (122,123), misdiagnosis of ICC as HCC on imaging studies may lead radiologists to skip histologic confirmation leading to improper treatment.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Moreover, functional information from gadoxetic acid-enhanced MRI has also been reported to be useful in the prediction of future remnant liver function (178,179), and US elastography or MR elastography can also provide predictive information for postoperative he-the sensitivity of brush cytology or tissue biopsy is not sufficiently high, as it was reported that the pooled sensitivity of brush cytology was only 43% (95% confidence interval: 35%, 52%) in detecting CC in patients with PSC (168), and endoscopic retrograde forceps biopsy showed sensitivities of approximately 50%-80% in malignant biliary strictures (169,170). Percutaneous transluminal forceps biopsy can also be performed via the percutaneous transhepatic biliary drainage tract, which demonstrated sensitivities of 77.2%-78.4% in malignant strictures (119,120). Considering this limited sensitivity, further evaluation or followup should be determined on the basis of imaging features for patients with negative histologic results.…”
Section: Perihilar CC Imaging Featuresmentioning
confidence: 99%
“…Sin embargo, el diagnóstico diferencial entre estenosis biliares benignas y malignas es en algunos casos desafiante, ya que en ambos tipos pueden presentar similar semiología imagenológica. Además, los tumores originados del epitelio de la vía biliar son, en un alto porcentaje, demasiado pequeños para visualizarlos por técnicas de imagen (3) .…”
Section: Discussionunclassified
“…En un estudio dirigido a valorar los factores asociados al rendimiento de la biopsia endobiliar con pinza de biopsia por acceso percutáneo, Park y colaboradores (3) demostraron que la sensibilidad y especificidad de la técnica son significativamente mayores en obstrucciones hiliares y en tumores originados del epitelio de la vía biliar. Esto podría estar relacionado a la dificultad de enfrentar la pinza de biopsia al sector central de la estenosis en tumores periampulares o del colédoco distal.…”
Section: Discussionunclassified
See 1 more Smart Citation